One Pot Synthesis and Characterization of Mono and Di-Substituted Azo-Containing Amides - Ahmad Khera, Rasheed; Iqbal, Munawar; Asif Tahir, M.; Asif Hanif, M.; Langer, Peter (Asian Journal of Chemistry, 2015)
Azo-containing amides and their derivatives were synthesized by the reaction of 4-(phenyldiazenyl)aniline with different substituted benzoyl chlorides. The characterization of these synthesized compounds were based on their IR, 1H NMR spectra and elemental analysis with excellent yields.